EptA of Riemerella anatipestifer mediates phenotypes involved in colistin resistance and virulence. Issue 5 (18th April 2023) - Chen, Qiwei; Quan, Heng; Yu, Yongfeng; Liu, Donghui; Li, Caiyu; Chu, Yuefeng; Gong, Xiaowei
Abstract: Colistin (polymyxin E) is a group of cationic antimicrobial cyclic peptides and is recognized as a last‐resort defense against lethal infections with carbapenem‐resistant pathogens. In addition to the plasmid‐borne mobilized phosphoethanolamine (PEA) transferases, the functional expression of lipid A‐modifying enzymes encoded on chromosomes has been attributed to intrinsic bacterial colistin resistance. However, the mechanisms of colistin resistance in Riemerella anatipestifer remain unknown. Herein, the GE296_RS09715 gene‐encoded Lipid A PEA transferases (RaEptA) was identified in R. anatipestifer . Genetic and structural analyses revealed that the amino acid sequence of RaEptA shared 26.6%–33.1% similarities with the family of Lipid A PEA transferases (EptA) and MCR‐like proteins and have defined 12 residues that contribute to the formation of phosphatidylethanolamine (PE)‐recognizable cavities. Comparative analyses of colistin resistance in RA‐LZ01 and RA‐LZ01ΔRaEptA showed the level of colistin has fallen from 96 μg mL −1 down to 24 ~ 32 μg mL −1 . Site‐directed mutagenesis assay of the PE‐binding cavity and expression of the mutants reveals that K309‐rRaEptA can remodel the surface of Escherichia coli and rendering it resistant to colistin, suggesting this point‐mutation of P309K is necessary for EptA‐mediated lipid A modification. Moreover, the virulence of RA‐LZ01ΔRaEptA was attenuated compared with RA‐LZ01 both in vivo and vitro. Taken together, the results represent the RaEptA involved in the colistin resistance and pathogenicity, and the P309K mutation might alter bacterial adaptation and increase the spread of colistin resistance from R. anatipestifer to other gram‐negative bacteria. The findings of this study suggest another scenario for the spread of colistin resistance genes and should be considered by a wide audience. Abstract : The R. anatipestifer RaEptA, a phosphoethanolamine transferase, which shown to confer intrinsic colistin resistance. RaEptA possess 1 crucial residue mutation (P309K) that play roles in the binding of RaEptA to the PE substrate molecule. RaEptA acts as a key virulence factor enhancing the pathogenicity of R. anatipestifer .